Sodium bicarbonate in the prevention of cardiac surgery-associated acute kidney injury: a systematic review and meta-analysis - Tie, Hong-Tao (BioMed Central, 2014)
INTRODUCTION: Sodium bicarbonate (SBIC) was reported to be a promising approach to prevent cardiac surgery-associated acute kidney injury (CSA-AKI). However, the results remain controversial. We conducted a systematic review and meta-analysis to evaluate the efficacy and safety of SBIC on the prevention of CSA-AKI in adult patients undergoing cardiac surgery. METHODS: PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases were systematically searched. Randomized controlled trials (RCTs) assessing the effect of SBIC versus placebo on the prevention of CSA-AKI in adult patients undergoing cardiac surgery were included. Two investigators independently searched articles, extracted data, and assessed the quality of included studies. The primary outcome was the incidence of CSA-AKI. Meta-analysis was performed using random-effects models. RESULTS: Five RCTs involving 1079 patients were included in the meta-analysis. Overall, compared with placebo, SBIC was not associated with a reduced risk of CSA-AKI (relative risk [RR] 0.99; 95% confidence interval [CI] 0.78 to 1.24; P = 0.911). SBIC failed to alter the clinical outcomes of hospital length of stay (weighted mean difference [WMD] 0.23 days; 95%CI −0.88 to 1.33 days; P = 0.688), renal replacement therapy (RR 0.94; 95%CI 0.49 to 1.82; P = 0.861), hospital mortality (RR 1.37; 95%CI 0.46 to 4.13; P = 0.572), postoperative atrial fibrillation (RR 1.02; 95%CI 0.65 to 1.61; P = 0.915). However, SBIC was associated with significant increased risks in longer duration of ventilation (WMD 0.64 hours; 95%CI 0.16 to 1.11 hours; P = 0.008), longer ICU length of stay (WMD 2.06 days; 95%CI 0.54 to 3.58 days; P = 0.008), and increased incidence of alkalemia (RR 2.21; 95%CI 1.42 to 3.42; P <0.001). CONCLUSIONS: SBIC could not reduce the incidence of CSA-AKI. Contrarily, SBIC prolongs the duration of ventilation and ICU length of stay, and increases the risk of alkalemia. Thus, SBIC should not be recommended for the prevention of CSA-AKI and perioperative SBIC infusion should be administrated with caution. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13054-014-0517-x) contains supplementary material, which is available to authorized users.